The Role of the Family in Internalizing Islamic Values - Ikhwan, Afiful; Biantoro, Oktio Frenki; Rohmad, Ali (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
Education is a conscious and planned effort that is applied to shape the character of a child who is characteristically and adheres to Islamic values in daily life. Thus the role of the family in providing education to children is very urgent to be applied in today's society which experiences moral decadence. The concept of religious values in children developed is the values of rabbaniyah and values of insanity. The steps of family involvement in internalizing ethical values in children are carried out through the stages of value transformation, value transactions, value internalization, and transcendalization of benefits by developing aspects of knowing, doing, and being. The element of knowledge is done by giving insight to children about religious values. The point of doing is made by guiding children. The aspect of being is done by providing an example to children. The three processes are not only carried out in schools but also carried out in the family with the guidance of parents. Also, in the process develops the concept of moral (moral knowing), honest attitude (good feeling), and ethical behaviour (moral behaviour).